2014
DOI: 10.1002/cbic.201402215
|View full text |Cite
|
Sign up to set email alerts
|

A Coenzyme‐Independent Decarboxylase/Oxygenase Cascade for the Efficient Synthesis of Vanillin

Abstract: Vanillin is one of the most widely used flavor compounds in the world as well as a promising versatile building block. The biotechnological production of vanillin from plant-derived ferulic acid has attracted much attention as a new alternative to chemical synthesis. One limitation of the known metabolic pathway to vanillin is its requirement for expensive coenzymes. Here, we developed a novel route to vanillin from ferulic acid that does not require any coenzymes. This artificial pathway consists of a coenzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 68 publications
0
57
0
Order By: Relevance
“…Substituted cinnamic acids are abundant molecules in plant lignin polymers and can provide feedstocks for microbial bioprocessing methods aimed at yielding value-added products (2, 3). Degradation of lignin releases ferulic and p-coumaric acids that can be converted to 4-vinylguaicol (4-ethenyl-2-methoxyphenol) and 4-vinylphenol (4-ethenylphenol), respectively, and other hydroxycinnamates can be metabolized to vanillin as a natural flavoring in foods, beverages, and other products (4,5). Related aromatic compounds are also natural components in wine and other fermented beverages and food (6)(7)(8).…”
mentioning
confidence: 99%
“…Substituted cinnamic acids are abundant molecules in plant lignin polymers and can provide feedstocks for microbial bioprocessing methods aimed at yielding value-added products (2, 3). Degradation of lignin releases ferulic and p-coumaric acids that can be converted to 4-vinylguaicol (4-ethenyl-2-methoxyphenol) and 4-vinylphenol (4-ethenylphenol), respectively, and other hydroxycinnamates can be metabolized to vanillin as a natural flavoring in foods, beverages, and other products (4,5). Related aromatic compounds are also natural components in wine and other fermented beverages and food (6)(7)(8).…”
mentioning
confidence: 99%
“…with the same enzyme but under the optimal conditions that they had worked out, especially with the addition of H 2 O 2 (as a co‐oxidant) and activated carbon (as an absorbent for the product), both of which have been found to be effective in enhancing the production yield . The conversion obtained in this study is also higher than that obtained using E. coli cells harbouring the decarboxylase/oxygenase cascade (1.2 g L –1 ), and is more than three times as high as that obtained by whole‐cell catalysis with Lysinibacillus fusiformis CGMCC1347 cells as the catalyst (0.7 g L –1 ) …”
Section: Resultsmentioning
confidence: 60%
“…Although many microorganisms have been studied extensively and a few enzymes in microbial cells have been identified for vanillin production, very few studies have focused on using isolated enzymes for this application. Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…Biotransformations with m-cresol (9) and 4-methoxy-2-methylphenol (6) demonstrated that the formation of methylhydroquinone (10) resulted from the conversion of m-cresol (9). No product formation of methylhydroquinone (10) was observed in the transformation of 4-methoxy-2-methylphenol (6). While F87V/A328L showed the highest conversion of 3-methylanisole (1) to intermediate product 3-methoxybenzyl alcohol (2) (9.1%), the highest production of 4-methylguaiacol (3) was achieved with the single variant A328L (2.7%).…”
Section: Screening Of the Small Focused Cyp102a1 Librarymentioning
confidence: 99%
“…The biotechnological synthesis of vanillin from ferulic acid has gained increasing attention in recent years. Artificial cascades combining a decarboxylase with an oxygenase were developed for the one-pot synthesis of vanillin [6,7]. Aiming at the enzymatic synthesis of vanillin by the selective hydroxylation of an aromatic substrate, cytochrome P450 monooxygenases (P450s) constitute ideal candidates [8].…”
Section: Introductionmentioning
confidence: 99%